2020
DOI: 10.1016/j.radcr.2019.11.019
|View full text |Cite
|
Sign up to set email alerts
|

4D-flow MRI assessment of blood flow before and after endovascular intervention in a patient with pulmonary hypertension due to isolated pulmonary artery involvement in large vessel vasculitis

Abstract: A 43-year-old woman presented with dyspnea during exertion and lower leg edema. Contrast-enhanced computed tomography images demonstrated extensive proximal narrowing in the right main pulmonary artery with thickening and enhancement. Right heart catheterization revealed the presence of precapillary pulmonary hypertension with a mean pulmonary arterial pressure of 45 mm Hg. The patient was diagnosed with large-vessel vasculitis with isolated pulmonary artery involvement. Takayasu's arteritis was suspected, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Kamada et al reported that stent treatment for unilateral pulmonary artery stenosis in large-vessel vasculitis resulted in an increase in overall pulmonary blood flow and improved blood flow balance between the right and left pulmonary arteries. 61 In CTEPH patients, 4D flow MRI allows for the demonstration of drastic changes in pulmonary blood flow after pulmonary thromboendarterectomy and BPA (Fig. 2e and 2f).…”
Section: Hemodynamic Effects Of Percutaneous Intervention For Group I...mentioning
confidence: 99%
“…Kamada et al reported that stent treatment for unilateral pulmonary artery stenosis in large-vessel vasculitis resulted in an increase in overall pulmonary blood flow and improved blood flow balance between the right and left pulmonary arteries. 61 In CTEPH patients, 4D flow MRI allows for the demonstration of drastic changes in pulmonary blood flow after pulmonary thromboendarterectomy and BPA (Fig. 2e and 2f).…”
Section: Hemodynamic Effects Of Percutaneous Intervention For Group I...mentioning
confidence: 99%
“…A variety of related proteins and acute phase proteins are expressed in the plasma of patients with TA, which can also be used to determine the different stages of the disease, and which are worthy of further discussion. In addition, the N-terminal pro-brain natriuretic peptide (NT pro-BNP) level was significantly higher in the PH group than the non-PH group, which may be related to the wide range of pulmonary artery lesions (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the efficacy of BPA may be smaller for patients with TA-PH and PPS compared with that in CTEPH [13]. In 2020, Kamada et al reported a patient of suspected TA with isolated pulmonary artery involvement complicated with severe PH, who underwent successful stent placement for stenosis in the right main pulmonary artery [19]. Mean PAP decreased from 45 to 22 mmHg and a concomitant increase in overall pulmonary blood flow, evaluated by 4D-flow cardiovascular magnetic resonance [19].…”
Section: Efficacy Of Bpa On Ta and Ppsmentioning
confidence: 99%